Eating habits and use of urban vegetable plants by residents of Balneário Camboriú, Santa Catarina, Brazil - Bastos, Fernanda Espíndola Assumpção; Santos, Angelita; Bacco, Pâmela Zottis de; Santos, Jerffson Lucas (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2023)
With the increase in technologies and the growth of cities, a large part of the population now lives in urban environments and consumes, mostly, vegetables, fruits, medicinal plants and spices purchased in supermarkets and/or fairs. It is necessary to encourage the use and creation of vegetable gardens in urban spaces, in order to promote better health for their users. The present work aimed to carry out a survey on eating habits and other information of a socioeconomic nature, in a sample of the population located in Balneário Camboriú -SC, through a questionnaire. From this survey, 10 people were randomly selected to participate in an extension program, where homegrown vegetable gardens were implemented in their residences using reused Styrofoam boxes. The present study resulted in the elaboration of homegrown vegetable gardens installed in 10 residences, in order to bring practical and theoretical knowledge about the importance of home gardens in the diet of its users. It was found that most respondents consume vegetables and fruits, so if there is a demand for these products, there is also a need to encourage and increase the number of actions to expand the production and consumption of food produced in urban environments, in order to reduce logistics costs and promote fresh and healthy food for the urban population.